PENGARUH BAURAN PEMASARAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN YANG BERDAMPAK PADA KEPUASAN KONSUMEN (Studi Kasus pada Konsumen Produk Merek Cardinal di Toko Trend Fashion Kendal) (Students' Journal of Economic and Management, 2014)
Consumer behavior is behavior that is shown consumers in finding , purchasing , using, evaluating, and spend the products and services that they expect will satisfy their needs . The purpose of this study was to analyze the effect of marketing mix and brand image on purchase decisions that impact customer satisfaction Sample of 100 people who the consumer is buying a product brand store Fashion Trend Cardinal in Kendal . Purposive sampling technique sampling is a sampling technique to the data source specific considerations. Consideration of the samples in this study is that consumers who have purchased a product brand store Fashion Trend Cardinal in Kendal more than once . Test equipment in this study using multiple linear regression. The results of the analysis can be concluded that : (1) marketing mix has a positive effect on purchase decisions. (2) The brand image has a positive effect on purchase decisions. (3) The decision to purchase a positive effect on customer satisfaction Keywords : marketing mix, brand image, purchase decision and customer satisfaction